Impact of innovative evidence-to-policy approaches on accelerating nutrition-related SDGs: Can the NIPN Model lead the way? - Zerfu, Taddese Alemu (Ethiopian Press Agency, 2024)
The global nutrition and food security crisis has reached alarming levels in recent years, with millions of people worldwide suffering from various forms of malnutrition - ranging from undernourishment to obesity. Food security remains a critical challenge. In 2021 and 2022, nearly one-third of the global population faced moderate to severe food insecurity, highlighting the persistent barriers to accessing healthy, sustainable diets. This has exacerbated the rise in malnutrition, with obesity and diet-related noncommunicable diseases (NCDs) becoming more widespread.